MODEL FOR EVALUATING THE INFORMATIVENESS OF SPECTRAL-PARAMETRIC DESCRIPTION OF TRANSFORMED VIDEO FRAGMENTS. - Tsimura, Yuri; Yudin, Oleksandr; Melnykov, Oleksandr; Koliadenko, Julia; Hurzhii, Paul (Science-based technologies, 2024)
The article substantiates that in modern conditions infocommunication technologies that use the wireless principle of data transmission are more developed. Approaches to the use of such technologies for the organization of information exchange with unmanned platforms are shown. This increases the efficiency of information processes in support and decision-making systems. At the same time, the article asserts the presence of problematic aspects. They are dictated by an imbalance between a certain level of intensity of the information flow that needs to be transmitted from the unmanned system and the level of throughput of on-board telecommunications facilities. To solve this problem, the article thoroughly proposes to use technologies for compressing video information flows. A study of modern methods of compression of video information streams is carried out. It is shown that they use platforms that are based on the encoding of transformed video fragments (VFR). One of the tested directions here is the formation of a spectral-parametric description of transformants. An example of such an approach is the construction of two structural components: the vector of the lengths of spectral bands and the vector of their significant levels. However, existing image compression technologies based on the JPEG platform do not provide the necessary efficiency of delivery of compressed video streams for a given level of visual quality of their visual perception after decompression. A model for estimating the informativeness of the transformer has been developed, which is presented in the spectral-parametric description by two components: the vector of the length of the SSB; vector of significant levels of the SSB. In this case, a limited number of permissible states of the SPT is taken into account on the basis of taking into account the current power of the alphabets of its two structural components. It is substantiated that as a result of the establishment of restrictions on the components of the structural components of SPT, conditions are created to reduce the amount of redundancy. It is shown that the amount of redundancy that can be reduced will increase in the case of: a decrease in the number of spectral subbands; decrease in the current power of the alphabet of significant components of the SSB.